(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Bharati Mukherjee’s main protagonists were not placed in a repressive socio-cultural setting,but rather in confusing milieus questioning their ethnicity, identity, and place of belonging. To defendtheir acts of assimilating with new culture and rejecting traditional principles, they attempt tocompromise with both old and new world ideals. The main character of the book, Tara, felt rooted lessnot just in her chosen home but also in her ancestral location among the folks she had grown up with.She experienced psychological trauma and social rejection in which no one showed her affection. Heremotional breakdown and isolation led to a point where she now feels alone and longs to return to heradopted home. Female identity is built in Mukherjee’s books using a variety of codes, elements,language, myth, history, psychology, gender, and race. It is closely related to both the subject’sunconscious inherited placement and their perception of themselves. These complications are reflectedin the development of this third place and its cultural locationality. Space offers history a dynamics all byitself. The type of interactions formed by the junction of power in the Diaspora mix of exclusion andinclusion in global ethnicities is significantly influenced by space.